Advanced Epitaxial Lift‐Off and Transfer Procedure for the Fabrication of High‐Quality Functional Oxide Membranes. Issue 2 (30th September 2022) - Bouaziz, Jordan; Cancellieri, Claudia; Rheingans, Bastian; Jeurgens, Lars P. H.; La Mattina, Fabio
Abstract: In the past 5 years, the transfer of epitaxial oxide thin films has drawn a renewed interest in the scientific community. The major challenge in this technology is to minimize the appearance of extended bulk defects such as plastic deformations, cracks, and delamination, which are induced by the transfer process to a new host substrate. In this work, a procedure for the transfer of epitaxial oxide films where a rigid bond to the final host holder is obtained via a metallic Au/Ag bonding layer is presented. Here, the transfer of SrRuO3 (SRO) and SrRuO3 /SrTiO3 (STO) epitaxial films grown on a water‐soluble Sr3 Al2 O6 sacrificial layer is reported. These epitaxial films are grown on a STO substrate and transferred onto a Si host substrate. Roughness values lower than 1nm are observed for the transferred SRO membranes. Cross‐section analysis shows straight interfaces without plastic deformation of the membranes. X‐ray diffraction rocking‐curve analysis evidences that mechanical damage is minimized and the membranes remain close to their initial quality. This procedure represents an important step forward in the development of advanced technologies for membrane transfer of epitaxial oxides and superstructures. Abstract : In this article, Bouaziz and co‐workers present a procedure for the transfer of epitaxial oxide films where a rigid bond to the final host holder is obtained via a metallic Au/Ag bonding layer. Cross section analysis and X‐ray diffraction show straight interfaces without plastic deformation of the transferred membranes.